(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
In the modern educational environment, the development of children’s creative abilities has become one of the key priorities of teaching and learning processes. STEAM education, which integrates Science, Technology, Engineering, Arts, and Mathematics, plays a significant role in fostering creativity, critical thinking, and problem-solving skills among learners. This article explores the concept of STEAM education, its pedagogical potential, and its role in developing children’s creative abilities. Special attention is given to the use of modern educational technologies, project-based learning, and interdisciplinary approaches within STEAM education. The study highlights the effectiveness of STEAM technologies in enhancing students’ imagination, innovation, and independent thinking.